1983
DOI: 10.1093/ajcn/38.3.356
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and precursor availability affect urinary catecholamine metabolite production in women

Abstract: The effect of obesity and tyrosine (tyr) supplements on catecholamine metabolism in 12 normal weight and nine obese adult women was studied. Protein intake was maintained at 1.4 g protein/kg fat-free mass daily for 4 days with tyr added (0.26 g/kg fat-free mass) to the liquid diet on the last 2 days. In the 12 normal subjects, but not the obese, base-line urinary excretion of the norepinephrine metabolite, 3-methoxy-4-hydroxy phenylethyleneglycol was related to body fat whereas excretion of the norepinephrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The 24 h urinary MHPG levels for the volunteers in this study are within the normal range reported in the literature [ Maes et al, 1989;Muscettola et al, 1984;Lensch et al, 1987;DeMet et al, 1985;Alonso et al, 1981;Dekirmenjian et al, 1970;Karege, 1984;Julien et al, 1988;Giedke et al, 1982;Wehr et al, 1980;Johnston et al, 1983 [ 19781 can be combined to make a direct comparison to the collection intervals in our study. Increases over the 0-4 h interval are more pronounced in our study (4-8 h, 33 vs. 9%; and 8-12 h, 59 vs. 30%) than in…”
Section: Discussionsupporting
confidence: 85%
“…The 24 h urinary MHPG levels for the volunteers in this study are within the normal range reported in the literature [ Maes et al, 1989;Muscettola et al, 1984;Lensch et al, 1987;DeMet et al, 1985;Alonso et al, 1981;Dekirmenjian et al, 1970;Karege, 1984;Julien et al, 1988;Giedke et al, 1982;Wehr et al, 1980;Johnston et al, 1983 [ 19781 can be combined to make a direct comparison to the collection intervals in our study. Increases over the 0-4 h interval are more pronounced in our study (4-8 h, 33 vs. 9%; and 8-12 h, 59 vs. 30%) than in…”
Section: Discussionsupporting
confidence: 85%
“…We therefore elected to allow our volunteers to maintain their usual dietary regimen and employed supplements of tyrosine calculated to approximately double their daily intake of this amino acid"; this was reflected by the twofold increase in tyrosine concentrations we observed in their plasma. A similar dietary program of supplemental tyrosine has been reported to maintain this relative increase for most of each 24-hour period 3 ' 15 and to enhance urinary excretion of metabolites of both norepinephrine and dopamine. 3 Brain tyrosine concentration reflects that in plasma.'…”
Section: Discussionmentioning
confidence: 98%
“…A similar dietary program of supplemental tyrosine has been reported to maintain this relative increase for most of each 24-hour period 3 ' 15 and to enhance urinary excretion of metabolites of both norepinephrine and dopamine. 3 Brain tyrosine concentration reflects that in plasma.' 6 -l7 Although this concentration appears to exceed the K m (25 /AM) for tyrosine hydroxylase, 18 the ratelimiting step for norepinephrine biosynthesis, studies have shown that an increase in brain tyrosine can lead to an increase in brain norepinephrine synthesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Certain drugs, e.g. L-dopa, are known to confound HVA estimation [10], as well as several dietary factors including vitamin B6 in combination with magnesium [11], nicotinamide adenine dinucleotide (NADH) used to treat patients with Parkinson's Disease [12], high monoamine meals in patients with Schizophrenia [13], and tyrosine supplementation in obese women [14]. These possible confounders are avoided prior to testing, under routine protocol.…”
Section: Introductionmentioning
confidence: 99%